Social Support and Medication Adherence Among People with Type 2 Diabetes Mellitus in Central Karnataka, India - Navinkumar Angadi; Shubha DB (Medsci Publications, 2023)
Background: Social support is crucial to improving the health of people with type 2 diabetes mellitus through medication adherence. Objectives: 1. To assess the social support and medication adherence among people with Type 2 diabetes mellitus. 2. To study the factors associated with social support and medication adherence among people with Type 2 diabetes mellitus. Methodology: This community-based study was undertaken among 150 people with type 2 diabetes mellitus. Social support was assessed using standard, validated Multidimensional Scale of Perceived Social Support. Medication adherence was assessed using standard, validated 8-item Morisky adherence scale. Results: Mean age of study participants was 57.42±11.07 years. In the present study 87 (58%) had high social support followed by moderate support 63 (42%). In the present study majority of study participants 83 (55%) had moderate medication adherence followed by low medication adherence 67 (45%). Conclusions: Social support plays an important role in promoting medication adherence among diabetes patients.